Isolation and Characterization of Indole-3-Acetic Acid Producing Bacteria from Cow Urine - Nisa Rachmania Mubarik; Iah Novi Maslahah (UIN Sunan Gunung Djati Bandung, 2019)
Cow urine contains urea as nitrogen source, therefore it can be expected to isolate the beneficial bacteria for plants, for example indole-3-acetic acid (IAA) or auxin producing bacteria. The objective of research was to obtain IAA producing bacteria from cow urine, to characterize bacterial isolate, and to measure its ability to stimulate the growth of green bean seedlings (Vigna radiata). The methods used in this study were collecting urine from cow cattle, obtaining IAA-pro-ducing bacteria from urine, measuring IAA using Salkowski method, and applying selected bacterial supernatants on green bean seedling plants. The number of IAA producing bacteria that was successfully purified was 18 isolates. There are five isolates, namely US 5, BS1, BS 2, BS 4 and BS 5 which have the ability to solubelize phosphate on Pikovskaya agar. The five isolates were also able to fix free nitro-gen on N Free media and did not show hypersensitivity on tobacco leaves. The results of the growth of isolates in blood agar showed positive for US 5 and BS 2 as beta hemolysin producers. Further-more, isolate BS 4 was chosen to produce exogenous IAA quantita-tively. Isolate BS 4 produced IAA 6.364 ppm at the 45 h incubation at stationary phase. The use of BS 4 supernatant on green bean seed-lings showed an effect on plant height and lateral root length better than control (without treatment) on 6 days after planting. Morpho-logical characteristic of isolate BS 4 was rod shape, Gram positive, endospore producing, aerobic, and had similarity with genus Bacillus